Effect of Dried Rumen Content with and Without Cellulase in Diet on Carcass Quality of Broiler Chickens - Mandey , Jet Saartje; Maaruf, Kartini; Regar, Mursye N.; Kowel, Youdhie H.S.; Junus, Christine (International Journal of Poultry Science, 2015)
The objective of the experiment was to assess the responses of broiler chicks to the inclusion of dried rumen content with and without cellulase on broiler diet. A total of 90 broiler chickens were used in this study. Broilers were randomly allotted to five dietary treatment groups and each treatment group was equally divided into three replicates. The dietary treatments were based diet (BD), 90% BD+10% Rumen Content (RC), 80% BD+20% RC, 90% BD+10% Rumen Content with Cellulase (RCC) (RC+0.5 g/kg cellulase), 80% BD+20% RCC, as R0, R1, R2, R3 and R4, respectively. The experiment terminated after 4 weeks at the age of 7 weeks, during which, feed intake, carcass yield, abdominal fat and blood cholesterol were measured. All experimental data were subjected to the analysis of variance test followed by orthogonal contrast test. Results showed that the daily feed intake of BD was significantly higher than RC and the RC was significantly higher than RCC, but no significant difference was observed between RCC 10 and 20%. Daily crude fibre intake of BD was significantly lower than RCC and RCC was significantly lower than RC. Carcass yield of BC was significantly higher than RC and RCC was significantly higher than RC and carcass yield was higher than RCC. Abdominal fat weight of RC was significantly lower than BD and RCC and the best abdominal fat weight was recorded in RC treatment. It can be concluded that rumen content without cellulase in diet could be acceptable for abdominal fat weight and rumen content incubated with cellulase could be acceptable up to 20% levels in broiler diets for carcass yield and blood cholesterol.